Discourse: Leader and the Modern Literature - Ainagul Ussenbekova, Bibizhan Begmanova, Yerkanat Khuatbekuly, Dina Yessenzhan Bibigul Sultanova (Opción, 2019)
In this article, we show political writings, thoughts and suggestions by Nazarbayev, his framework of discourse theory via comparative qualitative research methods. As a result, the poet is also a member of the people. We have stopped on verses to find out, Nazarbayev’s policy, communication with the people is how good. In conclusion, we have witnessed that Nazarbayev’s works contain not only elements of political discourse, but also argumentative, narrative, poetic and discourse.